Թեյշեբաինիի (Կարմիր-բլուր) պեղումներից հայտնաբերված ծխամանների նշանակության մասին - Զ. Մ. Ղասաբյան (ՀՍՍՌ ԳԱ հրատ․)
Во время археологических раскопок в Ване, Топрак-Кале и Тейшебаини были найдены глиняные сосуды в виде чаши на высокой ножке, с вертикальными прорезами на стенках (высота 15—28см) и в виде баночки цилиндрической формы, с круглыми отверстиями в верхней части (высота 8—15 см). During the archaeological excavations In Van, Toprak-Kale and Teyshebainy there were discovered earthenware vessels some cup-shaped on high leg with vertical openings on the sides (height 15—28 cm.) and the others in the shape of cylindrical pots with round holes in their upper part (height 8—15 cm.).
Keywords: Հնագիտություն